A new species of the genus Cnipsomorpha (Phasmatodea: Phasmatidae: Clitumninae) from China - Wang, San-Xing; Wu, Heng; Xie, Chong-Xin; Qian, Yu-Han (Zootaxa, 2026)
A new species named Cnipsomorpha liangheensis sp. nov. is described for the first time in this paper, which belongs to genus Cnipsomorpha Hennemann, Conle, Zhang & Liu, 2008. Detailed morphological descriptions were provided for both female and male. A key to identifying Cnipsomorpha is presented.